2019
DOI: 10.1002/jcp.28968
|View full text |Cite|
|
Sign up to set email alerts
|

XIST/miR‐376c‐5p/OPN axis modulates the influence of proinflammatory M1 macrophages on osteoarthritis chondrocyte apoptosis

Abstract: The inflammatory microenvironment in the joints is one of the critical issues during osteoarthritis (OA) and also the main factor that may aggravate symptoms. Under inflammatory microenvironment, M1 macrophages are activated and produce large numbers of proinflammatory mediators, leading to the production of degradative enzymes, the disturbance of chondrocyte apoptosis and cartilage catabolic processes, and finally the deterioration of OA. In the present study, we reveal that the overexpression of osteopontin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…There are conflicting reports regarding sOPN’s impact on macrophage polarization. Some of them show an M1 polarization mediated by OPN in osteoarthritis [64], whereas other research studies describe how M2 polarization is promoted by OPN fragments. This process is the result of an enhanced MMP production that degrades OPN [65].…”
Section: Reviewmentioning
confidence: 99%
“…There are conflicting reports regarding sOPN’s impact on macrophage polarization. Some of them show an M1 polarization mediated by OPN in osteoarthritis [64], whereas other research studies describe how M2 polarization is promoted by OPN fragments. This process is the result of an enhanced MMP production that degrades OPN [65].…”
Section: Reviewmentioning
confidence: 99%
“…Chondrocyte apoptosis and senescence have been detected in OA cartilage, which is associated with extracellular matrix (ECM) degradation [7,8] and participates in the initiation and development of OA [9][10][11]. Enhanced chondrocyte apoptosis has been re-ported to be significantly correlated with the severity of OA both in vitro and in vivo in studies of animals [12] and humans [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated OPN expression in OA [ 27 ]. Li et al [ 9 ] reported that OPN affects the pathogenesis of OA by regulating the level of macrophage-degrading enzyme. Wang et al [ 28 ] showed that OPN regulates synovial cell proliferation in OA.…”
Section: Discussionmentioning
confidence: 99%
“…However, Gao et al [ 8 ] demonstrated the high expression of OPN in the knee cartilage and synovial tissue of individuals with OA. Li et al [ 9 ] suggested that OPN can increase the apoptosis of OA chondrocytes by regulating the level of degradation enzymes in M1 macrophages; these results seem to be contrary to our experimental results that OPN plays a protective role in OA. But we believe that the secretion of OPN increases with the aggravation of arthritis, because the inflammatory factors stimulate the body to cause the protective high expression of OPN, and the enhancement of the apoptosis of M1 macrophages is actually to remove the degenerated chondrocytes in the joints, which may be beneficial to the body as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation